2010
DOI: 10.1007/s00247-010-1955-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimized T1- and T2-weighted volumetric brain imaging as a diagnostic tool in very preterm neonates

Abstract: Background T1-and T 2 -W MR sequences used for obtaining diagnostic information and morphometric measurements in the neonatal brain are frequently acquired using different imaging protocols. Optimizing one protocol for obtaining both kinds of information is valuable. Objective To determine whether high-resolution T1-and T 2 -W volumetric sequences optimized for preterm brain imaging could provide both diagnostic and morphometric value. Materials and methods Thirty preterm neonates born between 24 and 32 weeks'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(75 reference statements)
1
6
0
Order By: Relevance
“…30 The T1 (WM, 2636-2890 milliseconds; GM, 2113-2372 milliseconds) and T2 values (WM, 163-206 milliseconds; GM, 90-136 milliseconds) of preterm neonates of our study were consistent with a previous study that found T1 (WM, 2836-3045 milliseconds; GM, 1975-2196 milliseconds) and T2 values (WM, 216-255 milliseconds; GM, 153-167 milliseconds) for preterm neonates using spin echo-based sequences. 18 Gray matter also showed lower T1 and T2 values compared with WM in previous studies. 9,18,25 In preterm neonates, quantitative tissue characteristics can be used to differentiate brain regions.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…30 The T1 (WM, 2636-2890 milliseconds; GM, 2113-2372 milliseconds) and T2 values (WM, 163-206 milliseconds; GM, 90-136 milliseconds) of preterm neonates of our study were consistent with a previous study that found T1 (WM, 2836-3045 milliseconds; GM, 1975-2196 milliseconds) and T2 values (WM, 216-255 milliseconds; GM, 153-167 milliseconds) for preterm neonates using spin echo-based sequences. 18 Gray matter also showed lower T1 and T2 values compared with WM in previous studies. 9,18,25 In preterm neonates, quantitative tissue characteristics can be used to differentiate brain regions.…”
Section: Discussionmentioning
confidence: 65%
“…18 Gray matter also showed lower T1 and T2 values compared with WM in previous studies. 9,18,25 In preterm neonates, quantitative tissue characteristics can be used to differentiate brain regions. Accordingly, a previous study showed that diffusion tensor imaging parameters had sufficient sensitivity and specificity to differentiate brain regions such as the globus pallidus or putamen in preterm neonates.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…T 1 relaxometry measurements reported for neonates at term, preterm infants at term equivalent age and for preterm brain at birth showed lower T 1 values in GM structures compared to non-myelinated WM (Jones et al, 2004;Nossin-Manor et al, 2011;Williams et al, 2005). Furthermore, a study in healthy term-born infants from 3 to 11 months of age demonstrated lower T 1 values in GM structures compared to unmyelinated WM and in myelinated WM compared to GM structures (Deoni et al, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…It is affected by the presence of static internal fields, usually from protons of large molecules. T 2 values have been found to be an important diagnostic tool for assessing various disease pathologies [1].…”
Section: Introductionmentioning
confidence: 99%